Uji Aktivitas Antibakteri Ekstrak Daun Jambu Biji (Psidium guajava L.) terhadap Pertumbuhan Bakteri Escherichia coli - Niken Niken; Rahmi Novita Yusuf; Annita Annita (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Diarrhea is a disease that causes sufferers to have frequent bowel movements with watery or watery stools. One of the causes of diarrhea is Escherichia coli bacteria. One of the plants that has been used as an antidiarrheal is guava (Psidium guajava L.), especially the leaves. Guava leaves are known to contain phytochemicals, namely: tannins, flavonoids, alkaloids, saponins, and essential oils which function as antibacterials. This study aims to determine whether guava leaf extract can inhibit the growth of Escherichia coli bacteria. This research is a laboratory experimental study using the paper disc diffusion method (Kirby-Bauer). The sample used was Escherichia coli bacteria obtained from stool samples of diarrhea patients aged 8-12 years at the Nanggalo Health Center, Padang City, West Sumatra Province. The concentrations used in this study were 10%, 15%, 20%, and positive control for amoxicillin and negative control for distilled water. The results showed that the phytochemical test results for flavonoids, tannins and saponins, and alkaloids were positive. The antibacterial activity of guava leaf extract was shown to have inhibition against Escherichia coli bacteria with an average concentration of 10% with a diameter of 10.7 mm (strong), 15% with a diameter of 13.3 mm (strong), and 20% with a diameter of 17 mm (strong). ), 13 mm amoxicillin positive control, and 0 mm negative control. The results of the ANOVA test showed a value of p = 0.000 (sig. <0.05) that there was a significant difference between all treatments with a positive control. It can be concluded that guava leaf extract effectively inhibits the growth of Escherichia coli bacteria, this is because the diameter of the extract inhibition zone is larger than the positive control.